Contextual effects of color on food choices: Red ambient color induces indulgence - Szocs, Courtney; Abell, Annika; Ruzeviciute, Ruta; Kim, Yeseul; Biswas, Dipayan (Journal of Consumer Psychology, 2025)
Abstract This research examines how red ambient color in restaurants/cafeterias influences food choices. Prior research shows that red directly related to a food product (such as on nutrition labels or plates/cups) leads to avoidance of unhealthy foods. Yet, many successful fast‐food restaurants (e.g., McDonald's and Dairy Queen) use red in their ambiance, suggesting that in the context of food/eating, ambient red may have a different meaning than product‐related red. Indeed, the current research shows that consumers associate ambient red (e.g., wall color) with unhealthy restaurants. The presence of ambient red (vs. blue, gray, or white) leads to greater preference for unhealthy (i.e., high calorie, high fat, and indulgent) food options because consumers draw on ambient factors to make inferences about products sold in a retail establishment and then choose contextually appropriate products. The effect is moderated by the extent to which a consumer associates red with unhealthy restaurants. This research highlights how, in the context of food/eating, the placement of red influences its meaning and ultimately whether consumers approach or avoid unhealthy foods.